Upaya Pencegahan Kehamilan Resiko Tinggi yang Disebabkan "4 Terlalu" pada Wanita Usia Subur (WUS) di Desa Juntiweden Kabupaten Indramayu - Dartiwen Dartiwen; Cucu Nurmala (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
Fertile Age Women (WUS) are women whose reproductive organs function well between the ages of 20 and 45 years. In Juntiweden Village, there are still many pregnant women who have a high risk so that health workers need to develop practical skills to improve maternal health. One of our approaches is through community service activities by counseling women of childbearing age who aim to increase knowledge to prevent high-risk pregnancies caused by "4 Terlalu" as an effort to improve women's reproductive health. The counseling method uses adult learning methods, including discussion, question and answer, and video screenings. The description of the activity is carried out pretest in advance by using a questionnaire, giving material then carried out posttest. The results of the 50 people the number of participants found that before counseling (pretest) there were 44 people (88%) with less knowledge and six people (12%) with enough knowledge, whereas after being given counseling (posttest) results obtained 50 people (100%) good knowledge. This means that there is an increase in WUS knowledge about preventing high-risk pregnancies after getting counseling. This dedication activity can increase the knowledge of WUS in efforts to prevent high-risk pregnancies from reducing the number of maternal and infant deaths caused by 4 Terlalu.